Sifat Fisis dan Mekanis Papan Semen dari Serat Tandan Kosong Kelapa Sawit (The Physical and Mechanical Properties of Cement Board Made from Oil Palm Empty Fruit Bunches Fibers) - Purwanto, Djoko (Jurnal Riset Industri Hasil Hutan, 2016)
Oil palm empty fruit bunches (OPEFB) fiber were industrial waste that has not been widely used by the community, only stacked and cause odors that interfere with the surrounding environment. This research studied the utilization of OPEFB fiber for cement board products using cement as resin and CaCl2 as accelerator. Laboratory scale cement board made from OPEFB fiber were mixed with cement, and CaCl2. The composition of fiber and cement were 1:1, 1:1.5, 1:2, and CaCl2 variations were 0%, 1% and 3%. A mixture of fibers, cement and CaCl2 was compressed at the pressure of 4 ton for 24 hours. The cement boards were tested for physical and mechanical properties according to JIS A 5417-1992, and the results were compared to the requirements of the cement board JIS A 5417-1992. Cement board made from fiber and cement composition 1:1.5 and CaCl2 content 3% produced moisture content, thickness swelling, water absorption, density, modulus of rupture/MOR, modulus of elasticity/MOE and screw withdrawal strength that met the requirement of JIS A 5417-1992. The composition of fiber and cement and the variations of CaCl2 content produced significant effect on water content, water absorption, thickness swelling, modulus of rupture/MOR, modulus of elasticity/MOE and screw withdrawal strength on cement boards.Keywords : oil palm empty fruit bunches fiber, cement boards, physical and mechanical properties